Goldspotted spinefoot Siganus punctatus (Siganidae) age‐based reproductive life history and fisheries vulnerability. Issue 5 (25th September 2017) - Rhodes, K.; Hernandez‐Ortiz, D.; Ioanis, M.; Washington, W.; Maxim, S.; Olpet, K.; Malakai, S.
Abstract : Between February 2015 and 2016, samples of the Indo‐Pacific goldspotted spinefoot Siganus punctatus were taken from local fish markets, feeding sites and nursery grounds on the main island of Pohnpei, Micronesia, to ascertain sexual pattern, reproductive seasonality, age, growth and mortality. Microscopic examinations of gonads identified two seasonal peaks in reproduction: February to May and September to December, with evidence of some spawning activity in most months. Ripe females were observed 4 days on either side of the new moon. Females first matured at c . 180 mm fork length ( L F ) and 1 year of age, which coincides with their entry into the fishery. Ninety five per cent of individuals were less than 3 years and the oldest fish were 8 years. To examine the species vulnerability to fishing, a tag‐and‐recapture study was conducted over 4 months in 2015 in a locally managed marine area and at an unprotected site. Findings suggest high residency and high vulnerability to fishing at shallow‐water feeding sites and restricted migration overall. The placement of marine protected areas within critical habitat appears to be an effective conservation strategy for this species, particularly when combined with gear and seasonal market restrictions during vulnerable life‐history phases.